(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
Sports have a crucial role in the development of primary school children, not only physically but also mentally, emotionally, and socially. However, the downward trend in sports interest among children is of serious concern. This article discusses strategies to interest elementary school children in sports. This research uses literature study methods. This literature study is carried out by reading relevant sources to obtain the necessary data. The source of data or object of study used is scientific articles published in national journals through literature studies published through Google Scholar. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results of the analysis show that the strategy includes the creation of a school environment that supports physical activity, variations in the type of sport in the curriculum, a fun and interactive approach to learning, and the role of qualified sports teachers. Parental and community support is also important, by being a role model and providing opportunities to adapt in sporting activities. In addition, media and public policy can help raise awareness of the importance of sports for children. By implementing this strategy, it is hoped that primary school children’s interest in sports can increase, bring a positive impact on their health and well-being, and form a healthier and more active generation in the future